Suitability of Land in the Sapiang Island Group for Tourism Activities - Aprilia Ticoalu, Inneke Alya; Saputra, Iwan Alim; Widyastuti, Widyastuti; Maliki, Rendra Zainal (Department of Geography Education, Faculty of Social Sciences, Universitas Negeri Medan, 2025)
The Sapiang Island cluster has potential for tourism activities, especially beach tourism. Data from the Central Sulawesi Tourism Office shows a continuous increase from 2022 to 2024. The number of tourists in Central Sulawesi in 2024 is highest in April and December, while the lowest is in August. By district/city, the highest number of visits is in Palu city with a percentage of 24.1 percent, followed by Morowali Regency with 12.2 percent, Sigi Regency with 10.4 percent, and Donggala Regency with 9.8 percent. The objective of this research is to analyze and evaluate the land suitability level for tourism development. The method used in this research is a descriptive quantitative approach with a survey method. The data analysis was measured using coastal tourism land suitability analysis with bio-physical parameters modified by the researcher, with eight parameters. The results at the three points were categorized as Suitable (S1) with different percentages. The first observation point, Darat Island, received a score of 88.69%, while the second observation point, Bobonoan Island, received a suitability index score of 98.81%. The third observation point, Laot Island, received a suitability index score of 86.31%. The land suitability index results from the three observation locations conducted by the researchers obtained a value of 91.27%, which falls into the Suitable (S1) category for tourism activities. The results of the grouping of tourism activities based on physical parameters show that these physical parameters are dominant for beach recreation activities, with fourteen parameters being met.